Analisis Deiksis dalam Kumpulan Cerpen 'Setangkai Melati di Sayap Jibril' Karya Danarto - Atika Dewi; Natasya Fiqih Syahrani; Widzar Utom; Asep Purwo Yudi Utomo; Annisa Tetty Maharani; Rossi Galih Kesuma; Muhamad Majdudin (Pusat Riset dan Inovasi Nasional, 2024)
Language is a set of communication tools humans use to facilitate human life and carry out social interactions through oral and written communication. Pragmatics as a branch of semiotics and as a field of linguistic study, has one of the topics in the form of deixis, which is always present in communication and needs to be understood to answer confusion and obscurity. This article describes the use of deixis in literary works in the short story collection Setangkai Melati di Sayap Jibril. This study will analyze four titles of short stories for the use of deixis language: Sebatang Kayu, Mengapa Ayah Selalu Membuat Ibu Menangis, Matahari Menari, Rembulan Bergoyang, and Belimbing. Then, the approach used by researchers to analyze the short stories is theoretical in the form of a pragmatic approach and a methodological approach in the form of a descriptive-qualitative approach. Meanwhile, the data collection used in this research is the literature study, listening, and note-taking techniques. The data analysis technique used in this study is a split technique, while the method of presenting the results of data analysis uses the informal method. Based on the analysis that has been done, 1.108 deixis data are obtained in the form of social deixis (204), discourse deixis (187), persona deixis (520), place deixis (115), and time deixis (82). Therefore, writing the short stories in Setangkai Melati di Sayap Jibril is inseparable from using deixis.